Preparation of Char-Fe3O4 Composites from Polyvinyl Chloride with Hydrothermal and Hydrothermal-Pyrolysis Carbonization Methods as Co(II) Adsorbents - Muslem Muslem; Agus Kuncaka; Taffrika Nur Himah; Roto Roto (Universitas Gadjah Mada, 2019)
Char-Fe3O4 Composites have been synthetized through hydrothermal carbonization method and through hydrothermal-pyrolysis carbonization method by using polyvinylchloride as a carbon source. The products were characterized by FTIR, XRD, EDX, and TEM. The products were tested for Co(II) adsorption in water. The ability of Co(II) adsorption was studied for adsorption in different pH of the solution and its adsorption isotherm. Results showed that all products had similar hydrophilic functional groups and aliphatic carbon types. Char-Fe3O4 Composites produced by hydrothermal carbonization method (AFe-H) has more hydrophilic functional groups (C=O and –OH) than Char-Fe3O4 Composites produced by hydrothermal-pyrolysis carbonization method (AFe-P). Iron content was presented and distributed in the form of Fe3O4. Co(II) ion uptakes increased at the basic condition for all of the char-Fe3O4 Composites which were used as adsorbents. High hydrophilic functional groups in hydrothermal product composites (AFe-H) was the key factor contributing to the high adsorption ability with electrostatic interaction to the metal ion. AFe-H had the best Co(II) adsorption ability following the Langmuir isotherm model with its maximum adsorption capacity to be 0.556 mg g–1.